2015
DOI: 10.1161/circulationaha.114.013485
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Parental Smoking in Childhood Is Associated With Increased Risk of Carotid Atherosclerotic Plaque in Adulthood

Abstract: Background-The association between passive smoking exposure in childhood and adverse cardiovascular health in adulthood is not well understood. Using a 26-year follow-up study, we examined whether childhood exposure to passive smoking was associated with carotid atherosclerotic plaque in young adults. Methods and Results-Participants were from the Cardiovascular Risk in Young Finns Study (n=2448). Information on childhood exposure to parental smoking was collected in 1980 and 1983. Carotid ultrasound data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 36 publications
(24 reference statements)
5
42
0
Order By: Relevance
“…Considering clinical symptoms, 57.5% of patients had no symptoms and 42.5% showed clinical symptoms, including impaired movement, sensation, or language. Increased risk factors (e.g., current smoker, previous cardiovascular disease, previous cerebral vascular disease) have been previously reported in symptomatic patients (West et al, 2015;Niemann et al, 2017;Hoshino et al, 2018), and these traditional risk factors are closely related to carotid atherosclerosis (Redgrave et al, 2006;Virmani et al, 2006). We found that symptomatic patients were more likely to smoke (including present and ever) and have previous cardiovascular or cerebral vascular disease, despite the lack of significant differences in hypertension, diabetes, and dyslipidemia between groups.…”
Section: Discussionsupporting
confidence: 42%
“…Considering clinical symptoms, 57.5% of patients had no symptoms and 42.5% showed clinical symptoms, including impaired movement, sensation, or language. Increased risk factors (e.g., current smoker, previous cardiovascular disease, previous cerebral vascular disease) have been previously reported in symptomatic patients (West et al, 2015;Niemann et al, 2017;Hoshino et al, 2018), and these traditional risk factors are closely related to carotid atherosclerosis (Redgrave et al, 2006;Virmani et al, 2006). We found that symptomatic patients were more likely to smoke (including present and ever) and have previous cardiovascular or cerebral vascular disease, despite the lack of significant differences in hypertension, diabetes, and dyslipidemia between groups.…”
Section: Discussionsupporting
confidence: 42%
“…A report from the Young Finns Study indicated that offspring exposed to parental smoking in childhood had approximately twice the risk of having a carotid AS plaque in adulthood than did those with nonsmoking parents [ 49 ]. Carotid IMT in adulthood was greater in those exposed to smoking with both parents than in those whose parents did not smoke [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for the negative impact of childhood tobacco smoke exposure on cardiovascular health has been summarized in a scientific statement from the American Heart Association [35**]. A study in a Finnish population demonstrates how biomarkers of tobacco smoke exposure, specifically cotinine, are valuable tools in providing strong evidence of linkage between childhood exposure to tobacco smoke and increased risk of cardiovascular disease [36**]. Use of serum cotinine levels instead of parental self-report of smoking increased the relative risk of developing carotid plaques in adulthood from 1.7 to 4.0.…”
Section: Adverse Health Outcomesmentioning
confidence: 99%